Milly, Molly and the pumpkin seeds - Pittar, Gill; Morrell, Cris (Milly Molly Books Gisborne, N.Z., 2003)
Milly and Molly demonstrate social responsibility when they send pumpkin seeds to famine-struck Africa. Includes teaching guide. Suggested level: junior